PENGARUH PERKEMBANGAN LAHAN TERBANGUN TERHADAP KUALITAS LINGKUNGAN PERMUKIMAN (Studi Kasus: Kawasan Pendidikan Kelurahan Tembalang) - Yuliastuti, Nany; Fatchurochman, Arif (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2012)
The existence of educational activities in the Tembalang sub-district consequence the emergence of other activities to support educational activities, among other activities of living, trade and services and so on. The diversity of activity and increasing numbers of migrants implies built up area increasing for housing  and  supporting  facilities  and  infrastructure.  The  purpose  of  this  study  is  to  explain  the influence of built up area development to the quality of the settlement environment in the Tembalang educational  area.  This  study  uses  quantitative  methods  by  using  analytical  techniques,  including identification, correlative analysis, and descriptive analysis. Built up area developments in settlement area of Tembalang   from 2006 - 2010  increased for 48% (27 395  m2) from the  conditions at the beginning of the year 2006 with an average increase for 6848.77 m2 or about 12% of the area in 2006.  The  quality  of  settlement  environment  viewed from  the  physical  aspects  including  building density  conditions,  the basic coefficient  buildings, settlement  infrastructure and settlement  facilities show conditions are quite good quality. The condition of built up area development give a positive influence on scores from the quality of settlement environment by the equation Y = 0,256 x – 0,30. This means required at least 2% of built up area development which increase the quality of settlement infrastructure to improve the quality of settlement environments.